Chronic stress is associated with altered gut microbiota profile and relevant metabolites in adolescents - Li Ying; Wang Yuhao; He Yafang; Lan Jiao; Dang Lina; Song Qinze; Yang Chenghai; Zhao Shaoxiong; Gu Yuexi; Shen Mingwang; Cai Zelin; Wang Chuangchuang; et al. (BMC Microbiology)
Abstract Background Gut microbiota and microbiota-derived metabolites have been implicated in the regulation of stress-related diseases, yet their associations with chronic stress in adolescents remain unclear. Multi-omics studies on this topic in adolescents are still limited. This study aimed to characterize gut microbiota and metabolites in adolescents under chronic stress. Methods In this cross-sectional study, we assessed chronic stress in 124 adolescents aged 12–16 years using the Adolescent Life Events Scale and the Study Stress Scale. Participants were stratified by stress level into low (n = 42), medium (n = 41), and high stress (n = 41) groups. Fecal samples were collected from all participants for 16S rRNA gene sequencing. Subsequently, a subset of 30 adolescents with high stress and 29 low stress adolescents underwent metagenomic sequencing and untargeted metabolomics. Results Adolescents experiencing high-chronic stress showed lower alpha diversity, differential beta diversity, and a more complicated microbial network compared to those experiencing lower stress. Spearman’s rank correlation and Kruskal-Wallis test identified five genera with decreased abundances in high stress adolescents, including Faecalibacterium, Bacteroides, Akkermansia, Lachnospiraceae unclassified, and Ruminococcus (P fdr<0.05). Additionally, 12 species showed decreased abundances and 5 increased abundances, and logistic regression analysis further revealed that the relative abundances of Bifidobacterium catenulatum, Streptococcus suis, Ruminococcus sp. CAG 108, and Phascolarctobacterium faecium were associated with chronic stress (P fdr<0.05), after adjusting for sex, age, fruit consumption, and body mass index. We identified 21 differential metabolites, predominantly enriched in metabolic pathways based on KEGG analysis. Moreover, 19 out of these metabolites were significantly correlated with at least one of the four species significantly associated with chronic stress. These metabolites may explain health effects of species associated with chronic stress. Conclusions Chronic stress in adolescents is associated with altered gut microbiota composition and metabolite profiles, providing insights into possible mechanisms underlying stress-related diseases and highlighting the importance of longitudinal studies to clarify temporal and causal relationships.